The Demands of Performance Generating Systems on Executive Functions: Effects and Mediating Processes - Hansen, Pil; Climie, Emma A.; Oxoby, Robert J. (Frontiers in Psychology, 2020)
Performance Generating Systems (PGS) are rule- and task-based approaches to improvisation on stage in theatre, dance, and music. These systems require performers to draw on predefined source materials (texts, scores, memories) while working on complex tasks within limiting rules. An interdisciplinary research team at a large Western Canadian university hypothesized that learning to sustain this praxis over the duration of a performance places high demands on executive functions; demands that may improve the performers’ executive abilities. These performers need to continuously shift attention while remaining responsive to embodied and environmental stimuli in the present, they are required to inhibit automated responses and impulses using the rules of the system, and they strive towards addressing multitasking challenges with fluidity and flexibility. This study set out to test the mentioned hypothesis deductively and identify mediating processes inductively, using mixed empirical methods. In a small sample experiment with a control group (28 participants; 15 in intervention group, 13 in control group), standardized quantitative tests of executive functions (D-KEFS) were administered before and after an eight-week intervention. Participant-reported qualitative observations from the praxis were also collected throughout the intervention for grounded analysis. Within the limitations of small sample data, we found both statistically significant and trending effects on inhibition, problem-solving initiation, fluidity, and cognitive flexibility. Examining the mediating process, we found that participants experienced significant challenges sustaining the practice halfway through the intervention. The participant-reported solutions to these challenges, which emerged as the strongest behavioural patterns when coding the qualitative data to saturation, were strategies of problem-solving and of re-directing attention. These strategies support and advance our understanding of the effects measured in the standardized tests. In terms of application, our results identify characteristics of PGS that could potentially maintain and strengthen executive functions over and above less demanding performing arts interventions. The results also deliver new insight into how PGS works, which may contribute to the development and teaching of this artistic practice.